Bioengineering for vascularization: Trends and directions of photocrosslinkable gelatin methacrylate hydrogels - Im, Gwang-Bum; Lin, Ruei-Zeng (Frontiers in Bioengineering and Biotechnology, 2022)
Gelatin methacrylate (GelMA) hydrogels have been widely used in various biomedical applications, especially in tissue engineering and regenerative medicine, for their excellent biocompatibility and biodegradability. GelMA crosslinks to form a hydrogel when exposed to light irradiation in the presence of photoinitiators. The mechanical characteristics of GelMA hydrogels are highly tunable by changing the crosslinking conditions, including the GelMA polymer concentration, degree of methacrylation, light wavelength and intensity, and light exposure time et al. In this regard, GelMA hydrogels can be adjusted to closely resemble the native extracellular matrix (ECM) properties for the specific functions of target tissues. Therefore, this review focuses on the applications of GelMA hydrogels for bioengineering human vascular networks in vitro and in vivo. Since most tissues require vasculature to provide nutrients and oxygen to individual cells, timely vascularization is critical to the success of tissue- and cell-based therapies. Recent research has demonstrated the robust formation of human vascular networks by embedding human vascular endothelial cells and perivascular mesenchymal cells in GelMA hydrogels. Vascular cell-laden GelMA hydrogels can be microfabricated using different methodologies and integrated with microfluidic devices to generate a vasculature-on-a-chip system for disease modeling or drug screening. Bioengineered vascular networks can also serve as build-in vasculature to ensure the adequate oxygenation of thick tissue-engineered constructs. Meanwhile, several reports used GelMA hydrogels as implantable materials to deliver therapeutic cells aiming to rebuild the vasculature in ischemic wounds for repairing tissue injuries. Here, we intend to reveal present work trends and provide new insights into the development of clinically relevant applications based on vascularized GelMA hydrogels.